2012
DOI: 10.1002/pen.23191
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of precipitated calcium carbonate as a processing aid and impact modifier in poly(vinyl chloride)

Abstract: The effect of ultra-fine precipitated calcium carbonate (PCC), with a primary particle size of 50nm, on the fusion behaviour and mechanical properties of Ca/Zn stabilized poly(vinyl chloride) PVC has been investigated. The optimum concentration of PCC was determined and, in addition, experimental design was used to examine possible synergies between PCC and two important additives in a PVC-U formulation: namely, the processing aid and impact modifier. Dry blends were extruded and tested by Differential Scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Fernandes and Thomas examined the effect of various grades of precipitated and ground calcium carbonate on the tensile strength and Charpy impact energy of extruded PVC profiles [81,82]. The results confirmed that especially ultrafine precipitated calcium carbonate (UFPCC) can give rise to significant improvements in single notch impact strength.…”
Section: Inorganic Impact Modifierssupporting
confidence: 58%
“…Fernandes and Thomas examined the effect of various grades of precipitated and ground calcium carbonate on the tensile strength and Charpy impact energy of extruded PVC profiles [81,82]. The results confirmed that especially ultrafine precipitated calcium carbonate (UFPCC) can give rise to significant improvements in single notch impact strength.…”
Section: Inorganic Impact Modifierssupporting
confidence: 58%
“…The most common type of filler is calcium carbonate, as it is inexpensive, consistent, and readily available. It is also available in many different grades, making it more versatile than many other fillers 14,15 . As well as PVC resin, all PVC compounds will contain a stabilizer package.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the chemical treatment of kenaf fibers using hydrated chromium(III) sulfate ([Cr(H 2 O) 6 ] 2 (SO 4 ) 3 •6(H 2 O)) can also improve the mechanical, thermal, and morphological properties of LLDPE/PVOH/kenaf composites [5]. The use of precipitated calcium carbonate (PCC) as a filler in polymer materials has been widely developing because it includes natural materials that are abundant and easy to obtain [6][7][8][9][10]. PCC is calcite with an amorphous crystal structure and low hardness [11][12][13].…”
Section: ■ Introductionmentioning
confidence: 99%